Limitation of lithium fluoride (LiF) properties for passivation layer in organic solar cells application - Mohd Zain, Fadzly (2014)
Organic solar cell (OSC) is a low cost renewable energy. Instead of semiconductor silicon solar cell; it is a device that converts the energy of light into electrical energy using photovoltaic effect. Nowadays, global warming and emission of greenhouse effect are the sources of the destruction of our mother nature. One of the best organic solar cell is polymer-fullerene cell with poly (3-hexylthiopene) (P3HT) as the donor and the fullerene [6,6] - phenyl-C61 butyric acid methyl ester (PCBM) as the acceptor. The organic solar cell preparation in a lot of research is prepared by the evaporation of organic solar cell layers. This method seems impractical in the largescale production because the vacuum step requires large power supply. The solar cell preparation using spin coating techniques are the most compatible. As a conclusion, Lithium Fluoride (LiF) prevent metal electrode from diffusing into PEDOT: PSS (poly (3,4-ethylenedioxythiophene) poly(styrenesulfonate)) and ITO (Indium Thin Oxide) because LiF is an interfacial chemistry model for metal cathode that act as a buffer layer and coupling layer to enhance electron injection. Lithium Fluoride can also enhance metal cathode performance, characterize Lithium fluoride (LiF) thickness and test LiF as interlayer between active layer and metal layer by using solgel method to improve metal cathode performance if the thickness is less than 10nm.